A crushing analysis and multi-objective optimization of thin-walled five-cell structures - Bigdeli, Ali; Nouri, Mohammad Damghani (Thin-walled structures, 2019)
The present paper introduces two types of inner cellularization geometry in the thin-walled cylinders derived from previous studies on this area of subject. Novel geometries were proposed in this research. These configurations were the result of modifications to the previous works. Moreover, these absorbers were proposed to increase the specific energy absorption, reduce the peak energy, and improve crushing. The maximum Specific Energy Absorption (SEA), minimum Initial Peak Crushing Force (IPCF) under quasi-static axial compression test at the rate of 10 mm/min, and thickness and height parameters of the thin-walled cylinder and length of the inner square's sides were considered the design variables to achieve the optimal state. In the present work, two DOEs (design of experiment) were performed in Design-Expert in accordance with the given surfaces for both geometries of the thin-walled cylinder's inner cores. Subsequently, for further investigation, the experimental results were compared with those obtained from the finite element simulation in Abaqus, revealing the desirable accuracy of the results. Finally, by applying the equations derived from the proposed model to each of the responses and geometries, their optimal states were obtained using both the desirability approach in Design-Expert and the MOPSO method in MATLAB. Thickness had the highest impact on both configurations. Moreover, the optimal thickness for both configurations was 1.4 mm in the selected range. As regards the multi-objective function, the best inner square edge lengths for the C2R and S2R configurations were the central and upper limits, respectively. Finally, the cylinder heights for the C2R and S2R geometries were 174 and 153 mm, respectively. •The present paper introduces two types of inner cellularization geometry in the thin-walled cylinders derived from previous studies on this area of subject. In the present investigation, the quasi-static compressive experimental and numerical simulation test cylindrical absorbers is discussed.•The thin-walled cylindrical energy absorbers are considered with combined hybrid geometries and novel internal cells.•The response surface method (RSM), which is one of the design of experiments (DOE) techniques has been used to examine the effect of the parameters on energy absorption.•The equations derived from the proposed model for each of the responses and each geometry.•Optimal states were also obtained using both the desirability approach in Design Expert software and MOPSO method in MATLAB software.